EMPLOYEE ENGAGEMENT CAN MODERATE THE EFFECT OF TRANSGLOBAL LEADERSHIP ON EMPLOYEE PERFORMANCE - Nasution, Ucok Binanga; Prihadini, Diana; Fitri, Nur; Widiasih, Suprapti (ITB AAS Indonesia Surakarta, 2024)
ABSTRACTThis study is a quantitative study with an explanatory approach, namely an approach that uses previous literature as a support for the arguments being discussed. The data used in this article is primary data that researchers obtained from BUMN leaders and employees spread throughout Indonesia. The conclusion in this research show that the Transglobal Leadership variable can have a positive relationship direction and a significant influence on Employee Performance can be proven. This is due to the P-Values which are positive and below the significance level of 0.05, namely 0.001. This is because the Intelligence of the Leader and the Wisdom of the Leader in creating policies that can facilitate employee tasks can ultimately improve Employee Performance. In addition, in the next hypothesis, the Employee Involvement variable can strengthen the influence of the Transglobal Leadership variable on Employee Performance. This is because the same thing, namely the P-Values value is positive and below the significance level of 0.05, namely 0.000, which is smaller than direct testing of 0.001. Thus, it can be concluded that the first and second hypotheses can be accepted. Keywords: Transglobal Leadership, Employee Performance, Employee Engagement